(untitled) (Journal of the College of Basic Education, 2022)
The current study was conducted on 40 control females, ages 40-50 years, while the patient group included 40 patients with subclinical hypothyroidism, ages less than 40 years (20 patients) and between 40-50 years (20) patients, and from reviews to the specialized center for endocrinology And diabetes near Al-Kindi Hospital / Al-Rusafa, Baghdad Governorate, and treatment with levothyroxine. The results showed a non-significant increase (P>0.05) in TSH levels for the age group less than 40 years, with an average mu / L (1.67 ± 6.28), as well as in the age group 40-50 years, with an average of 1.5 mu /L) ± (6.82) compared with the control group (4.07 ± 0.09mu/L), except that the values ​​of the TSH level in both groups of patients were higher than the normal values ​​of the TSH hormone